Optimization of bronchial asthma treatment according to polymorphism in the leukotriene-C4 synthase gene - Cherednichenko, Nataliia; Kochuieva, Maryna; Tymchenko, Hanna; Zaikina, Yulia; Kochuiev, Gennadii; Liashok, Andrii (ScienceRise: Medical Science, 2021)
The aim of the study was to investigate the effectiveness of different schemes of basic asthma therapy depending on the polymorphism of the LTC4 gene. Materials and methods. 181 patients with asthma were recruited to participate in the study. All patients included in the study underwent a general clinical study, spirometry, the level of asthma control was determined by Asthma control questionnaire 5 (ACQ-5), by studying the polymorphism of the LTC4 gene, it was determined that patients belong to the A/A, A/C and C/C genotypes. Results. Allelic -444C polymorphism of the LTC4-S gene (rs 730012) had the following genotype frequency among asthma patients: A/A – 77 people (42.6 %), A/C – 73 people (40.3 %) and C/C – 31 people (17.1 %). In groups of patients with genotypes A/A and A/C, during treatment with a low dose of ICS and montelukast, there was a significant improvement in FEV1 and the score according to the ACQ-5 questionnaire (asthma control level). However, in the group of patients with the C/C genotype, there were no significant changes in FEV1 and the score according to the ACQ-5 questionnaire. In the groups of patients with genotypes A/A and C/C on the background of increasing the dose of ICS to medium in a fixed combination with LABA compared with the results of treatment with low-dose ICS and montelukast, there was a significant improvement in FEV1 and asthma control – ACQ- 5. At the same time, in the group of patients with genotype A/C, there were no reliable indicators of FEV1 and ACQ-5 score changes. Conclusions. The frequency of genotypes A/A, A/C and C/C for LTC4S polymorphism in the studied population are 42.6 %, 40.3 % and 17.1 %, respectively. Patients with genotypes A/A and C/C have a significant response to treatment with a low dose of ICS and montelukast in the form of an improvement in FEV1 and ACQ-5 score. Increasing the dose of ICS up to moderate in a fixed combination with β2-LABA in groups of patients with genotypes A/A and C/C leads to a significant improvement in the FEV1, as well as in the asthma control level - ACQ-5